The Effect of Dexmedetomidine on Postoperative Nausea and Vomiting in Patients Undergoing Thoracic Surgery-A Meta-Analysis of a Randomized Controlled Trial - Zhang, Wei; Wang, Ruohan; Li, Bing; Zhao, Ying; Liu, Xinmin; Yuan, Jingli (Frontiers in Surgery, 2022)
Background Dexmedetomidine reduces the occurrence of postoperative nausea and vomiting (PONV); however, the effect of dexmedetomidine on PONV in patients undergoing thoracic surgery remains inconclusive. In addition, the effect of different dexmedetomidine application methods, anesthetics, and surgical procedures on the effects of dexmedetomidine on PONV remains unclear. Therefore, the purpose of this meta-analysis was to study the effect of dexmedetomidine on PONV in patients undergoing thoracic surgery. Methods Electronic databases were searched to identify randomized controlled trials studying the effects of dexmedetomidine on nausea and vomiting after thoracic surgery. In total, 12 articles that met the inclusion criteria were obtained. The primary outcome of this comprehensive analysis was the incidence of PONV; secondary outcomes included the incidence of postoperative nausea, the incidence of postoperative vomiting, postoperative visual analog score (VAS), the amount of intraoperative sufentanil, and the number of times postoperative salvage analgesia was administered. Results Twelve trials involving 905 participants undergoing thoracic surgery were included. Compared with placebo, dexmedetomidine reduced the incidence of nausea and vomiting after thoracic surgery [12 trials; 905 participants; risk ratio (RR) = 0.32; 95% CI (0.23, 0.44); P < 0.00001, I2 = 0%]. The subgroup analysis revealed that dexmedetomidine reduces the occurrence of PONV in both thoracotomy and thoracoscopic surgery. In addition, both intravenous and local infusion of dexmedetomidine can reduce the occurrence of PONV, and intravenous or inhaled anesthetics do not affect the effect of dexmedetomidine on reducing PONV. Dexmedetomidine can reduce the postoperative resting VAS of patients, and no statistically significant differences in the amount of intraoperative sufentanil and the number of salvage analgesia procedures after surgery were noted. Conclusion Compared with placebo, dexmedetomidine can reduce the occurrence of PONV in patients undergoing thoracic surgery, and this effect is not affected by the method of dexmedetomidine administration, use of minimally invasive surgery, and use of a combination of intravenous or inhalation anesthetics. Systematic Review Registration https://www.crd.york.ac.uk/prospero/#myprospero, PROSPERO, identifier: CRD42021269358.